Editorial - Ewertsen, Caroline (Ultrasound International Open, 2017)
Dear Colleagues,It is with pleasure that I hereby introduce the ninth issue of UIO.This issue covers a wide range of interesting topics. Some of the topics are also focus areas for the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB), namely student education in ultrasound and elastography. Guidelines are available under www.efsumb.org.